Recent Advances in the Cellular and Developmental Biology of Phospholipases in Plants - Takáč, Tomáš; Novák, Dominik; Šamaj, Jozef (Frontiers in Plant Science, 2019)
Phospholipases (PLs) are lipid-hydrolyzing enzymes known to have diverse signaling roles during plant abiotic and biotic stress responses. They catalyze lipid remodeling, which is required to generate rapid responses of plants to environmental cues. Moreover, they produce second messenger molecules, such as phosphatidic acid (PA), and thus trigger or modulate signaling cascades that lead to changes in gene expression. The roles of phospholipases in plant abiotic and biotic stress responses have been intensively studied. Nevertheless, emerging evidence suggests that they also make significant contributions to plants’ cellular and developmental processes. In this mini review, we summarized recent advances in the study of the cellular and developmental roles of phospholipases in plants.